PENGARUH PENGUASAAN KOMPETENSI PEDAGOGIK, KOMPETENSI KEPRIBADIAN, KOMPETENSI PROFESIONAL DAN KOMPETENSI SOSIAL TERHADAP KINERJA GURU SMKN 2 WONOSOBO TAHUN PELAJARAN 2013 / 2014 (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
This research aims at determining the impact of pedagogical, personality, professional, and social competency mastery towards teacher of SMKN 2 Wonosobo performance in academic year 2013 / 2014.The qualitative research is correlative in nature, i.e. finding correlation between variables shown in coefficient correlation numbers. The data were collected by questionnaire which its reliability and validity have been tested before. The questionnaire testing was conducted to 30 teachers of SMKN 1 Sapuran as respondents. The research population is the teachers of SMKN 2 Wonosobo which was stated by random sampling and nomogram Herry King with an error rate of 5%. The data analysis used SPSS 16.0 before analized, the data were tested about its prerequisite normality, linearity, and multicolinearity. The data analysis were multiple regression, and partial correlation.The research result shows that pedagogical, personality, professional, and social competency commands either conducted integratively or separately give very convincing and positive impact towards teachers of SMKN 2 Wonosobo performance in academic years 2013/2014. The higher the pedagogical, personality, professional, and social competency command either integratively or separately, he higher the teachers’ performance. On the contrary, the lower pedagogical, personality, professional, and social commands integratively towards teacher of SMKN 2 Wonosobo performance in academic year 2014 is 31,3% and the impact from the other factors is 68,7%. Separately, pedagogical competency command towards teachers’ performance give the biggest impact i.e 16,1% while personality competency command give the least impact 10,6%, professional competency command gives the least impact, i.e. 0,2% and social competency command gives impact 3,4%.